Pengembangan Keterampilan Teknologi Informasi bagi Anak Yatim dan Kurang Mampu di Yayasan Ahmad Al-Badriah, Tangerang dengan Pelatihan Dasar Microsoft Office 2010 - Safitri Juanita; Dolly Virgian Shaka Yudha Sakti; Muhammad Anif (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
In today's world, the ability to comprehend information technology is crucial, as it is used in nearly every aspect of daily life. The Ahmad Al-Badriah Foundation in Tangerang City takes care of orphans and poor kids who don't know how to use technology, especially computer applications. Together with the Ahmad Al-Badriah Foundation in Tangerang City, FTI proposed training in Microsoft Office. This Community Service Activities (CSA) aim to improve ICT skills or competencies for orphans and poor children so that they can learn, gain experience, and help training participants improve their skills in using information technology, which can help them do their schoolwork or jobs that use computer applications. In this CSA activity, the method starts with figuring out what the partner needs are, then doing MOUs, making modules, doing training activities, and getting feedback. The conclusion of this activity is that the Ahmad Al-Badriah Foundation in Tangerang has shown that training in Microsoft Office 2010 programs like Microsoft Word and Microsoft Power Point can help orphans and other children who don't have much improve their IT skills. This is clear from the fact that 55% of the people who took the training said they strongly agreed that it would improve their skills and 41% said they agreed